Self-Regulated Learning is not for Everyone: Towards an Explanation for the Heterogeneous Effects of Interventions - M. S. Khamidulina; N. G. Maloshonok (Высшее образование в России)
The learning success of students depends largely on the extent to which they have developed self-regulated learning skills. These are expressed as a set of cognitive, behavioral, and motivational strategies that help students set learning goals, develop a sequence of actions to achieve them, control their behavior and surrounding circumstances, and reflect on the outcomes of their learning. Existing research shows that many students have difficulty completing courses that require a high degree of student autonomy (e.g., online courses). And these difficulties are due to the fact that selfregulated learning skills are weak among students. To develop these skills, special interventions are used, which take the form of lectures, assignments and comprehensive training courses. However, research shows that such interventions have a heterogeneous effect: They can lead to an increase in skills for some socio-demographic groups, while being ineffective for other groups of students. The observed heterogeneous effect of interventions has not yet been explained, which prevents the development of an effective strategy to improve self-regulated learning skills in all students. This paper attempts to explain this phenomenon using qualitative research. Interviews were conducted with students who participated in the comprehensive intervention “Self-regulated learning: how to develop self-control and metacognition”. Based on these data, a conceptual model was created that explains the differences in the effectiveness of interventions depending on the individual characteristics of the students and the characteristics of the intervention itself. The findings formed the basis for practical recommendations for the development and implementation of interventions to develop self-regulated learning skills in universities. The article will be of interest to researchers in the field of pedagogy and educational psychology, teachers and methodologists at universities, as well as managers whose activities are related to the organization of the educational process.